2022
DOI: 10.1021/acs.nanolett.1c05028
|View full text |Cite
|
Sign up to set email alerts
|

Tip-Induced In-Plane Ferroelectric Superstructure in Zigzag-Wrinkled BaTiO3 Thin Films

Abstract: The complex micro-/nanoscale wrinkle morphology primarily fabricated by elastic polymers is usually designed to realize unique functionalities in physiological, biochemical, bioelectric, and optoelectronic systems. In this work, we fabricated inorganic freestanding BaTiO 3 ferroelectric thin films with zigzag wrinkle morphology and successfully modulated the ferroelectric domains to form an in-plane (IP) superstructure with periodic surface charge distribution. Our piezoresponse force microscopy (PFM) measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In addition to the domain switching, more importantly, Dong et al found the continuous rotation of dipoles in the transition region connecting a- and c-domains. The formation of the transition region could buffer the strain mismatch between the a- and c-domains, which prevents brittle fracture in the wrinkled BTO membranes. ,, The emergence of domain variants leads to a decrease in the domain wall energy and overall energy barrier for the domain nucleation during polarization switching, which could potentially contribute to a decrease in the coercive field. In Figure b, we have summarized the magnitude of the imprint, defined as ( V c+ + V c– )/2, as a function of strain (ε 0 ). With the strain improving, no matter whether the strain state is tensile or compressive, the magnitude of the imprint increases from ∼ −0.04 to ∼0.61 V in the tensile strain state and from ∼ −0.04 to ∼ −0.41 V in the compressive strain state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the domain switching, more importantly, Dong et al found the continuous rotation of dipoles in the transition region connecting a- and c-domains. The formation of the transition region could buffer the strain mismatch between the a- and c-domains, which prevents brittle fracture in the wrinkled BTO membranes. ,, The emergence of domain variants leads to a decrease in the domain wall energy and overall energy barrier for the domain nucleation during polarization switching, which could potentially contribute to a decrease in the coercive field. In Figure b, we have summarized the magnitude of the imprint, defined as ( V c+ + V c– )/2, as a function of strain (ε 0 ). With the strain improving, no matter whether the strain state is tensile or compressive, the magnitude of the imprint increases from ∼ −0.04 to ∼0.61 V in the tensile strain state and from ∼ −0.04 to ∼ −0.41 V in the compressive strain state.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the transition region could buffer the strain mismatch between the a-and c-domains, which prevents brittle fracture in the wrinkled BTO membranes. 30,31,33 The emergence of domain variants leads to a decrease in the domain wall energy and overall energy barrier for the domain nucleation during polarization switching, which could potentially contribute to a decrease in the coercive field. 34−36 In Figure 4b, we have summarized the magnitude of the imprint, defined as (V c+ + V c− )/2, as a function of strain (ε 0 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The formation of various wrinkled structures has been reported in thin film systems such as metals [126] , graphene [132] , organics [130,131,133,134] , gels [147] , biological tissues [148] and more recently in freestanding ferroelectric thin film systems. As shown in Figure 7A, Dong et al successfully fabricated periodic wrinkle-patterned BTO/PDMS membranes based on an as-prepared super-elastic single-crystal freestanding BTO film [63,64] . Moreover, finely controlled wrinkle patterns, such as sinusoidal, zigzag and labyrinthine patterns, were obtained by changing the anisotropy and magnitude of the applied stress or adjusting the interfacial adhesion conditions.…”
Section: D Wrinkled Structure Of Freestanding Ferroelectric Thin Filmsmentioning
confidence: 99%
“…(H) The electric toroidal moments corresponding to the domain structure in (G) illustrate the presence of in-plane topological domains. Panel A reprinted with permission [63] . Copyright 2020, Wiley-VCH.…”
Section: D Wrinkled Structure Of Freestanding Ferroelectric Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation